Institutional investors in global capital markets - Boubakri, Narjess; Cosset, Jean-Claude (Emerald, 2011)
The edited volume on The Role of Institutional Investors in a Globalized Environment will publish original papers that examine various issues concerning the strategies of institutional investors, the role of institutional investors in corporate governance, their impact on local and international capital markets, as well as the emergence of sovereign and other asset management funds and their interactions with micro and macro economic and market environments including the impacts on international economic and market stability.
Keywords: Institutional investments.; Institutional investors.; Global custody (Securities); Business & Economics -- Banks & Banking.; Business & Economics -- Finance.; Finance.; Banking.; elektronické knihy; electronic books